A Review of Recent Trends in High-Efficiency Induction Motor Drives - Mohamed Azab (Vehicles)
Induction motor (IM) drives are considered one of the important technologies in modern industry. Several industrial applications, such as material handling and food and beverage applications, are driven and operated by modern AC drives. Moreover, modern electric transportation systems such as EVs and e-trucks are based on AC drives. Recently, high-efficiency IM drive systems have been studied as a major opportunity to reduce energy and fuel consumption. This article addresses the recent trends and advancement in high-efficiency IM drives during a particular period (2017–2024), including the development of high-efficiency motors, the utilization of efficient wide bandgap (WBG) semiconductor devices for inverter topology, and commonly used control strategies to achieve high-performance drives. Moreover, the article addresses several manufacturers of industrial IM drives and the corresponding adopted control techniques in their products. A comparison of these control techniques, including their pros and cons, has been conducted as well.